2012
DOI: 10.1680/coma.11.00023
|View full text |Cite
|
Sign up to set email alerts
|

Humidity buffering using stabilised rammed earth materials

Abstract: Citation: ALLINSON, D. and HALL, M., 2012 The humidity buffering potential of stabilised rammed earth materials is investigated based on the moisture buffer value concept. The moisture buffer value is (a) measured experimentally, (b) calculated from an analytical solution of the mass transfer and (c) simulated using a numerical solution of the combined heat and mass transfer. The numerical solution to the equations is described, as well as the modelling tool termed 'CHAMP' (coupled heat and mass transport in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…MBV results confirmed that unstabilised RE is a good passive air conditioner and that this ability is highly affected by the soil's characteristics [18,42,43]: P and ELS had a very positive MBV but presented a marked difference between the results. The difference among the results was generated by the different porosity and soil mineralogy of the mixtures: P had both a higher bulk and very fine porosity and a more hygroscopic clay fraction (mainly Illite, more hydrophilic than kaolinite, the main component of the clay fraction of ELS [44][45][46]), improving its MBV over ELS.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…MBV results confirmed that unstabilised RE is a good passive air conditioner and that this ability is highly affected by the soil's characteristics [18,42,43]: P and ELS had a very positive MBV but presented a marked difference between the results. The difference among the results was generated by the different porosity and soil mineralogy of the mixtures: P had both a higher bulk and very fine porosity and a more hygroscopic clay fraction (mainly Illite, more hydrophilic than kaolinite, the main component of the clay fraction of ELS [44][45][46]), improving its MBV over ELS.…”
Section: Discussionsupporting
confidence: 59%
“…A few studies have recently been published focusing on the humidity buffering potential of stabilised rammed earth (SRE) and compressed earth blocks, concluding that modern compressed earth can be a good moisture buffering material [18][19][20]. Other authors studied earthen plasters and advised the addition of aggregates in the mixture, such as natural fibres or synthetic gels, to enhance their hygroscopic properties [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…More recently non peer reviewed reports were published in Germany by Eckermann and Ziegert [9] on the influence of unfired clay masonry on the interior room climate. Researchers in the UK have investigated the hygrothermal and moisture buffering performance of stabilised rammed earth walls [10,11]. In some cases the clay material was studied in combination with other materials such as organic waste [12] or fibrous materials such as hemp [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…A second feature of earthen materials is their well-established ability to store Fifth International Conference on Sustainable Construction Materials and Technologies. http://www.claisse.info/Proceedings.htm and manage heat which guarantee interior comfort in shelters (Heathcote, 2011;Allinson and Hall, 2012;Pacheco-Torgal and Jalali, 2012;Soudani et al, 2016).…”
Section: Introductionmentioning
confidence: 99%